A Chinese Herbal Formulation, Xiao-Er-An-Shen Decoction, Attenuates Tourette Syndrome, Possibly by Reversing Abnormal Changes in Neurotransmitter Levels and Enhancing Antioxidant Status in Mouse Brain - Chen, Jihang; Leong, Pou Kuan; Leung, Hoi Yan; Chan, Wing Man; Li, Zhonggui; Qiu, Jingyu; Ko, Kam Ming; Chen, Jianping (Frontiers in Pharmacology, 2019)
Xiao-Er-An-Shen Decoction (XEASD) has been used clinically for the treatment of Tourette syndrome (TS) in children for more than 20 years in mainland China. The biochemical mechanism underlying the therapeutic action produced by XEASD treatment against TS remains unknown. However, a previous study has shown that pre-incubation of PC12 neuronal cells with XEASD can induce neurite outgrowth and protect against oxidative stress. In the present study, using a mouse model of TS induced by 3,3’-iminodipropionitrile (IDPN), stereotypy scoring, and locomotor activity were assessed. Levels of neurotransmitters including glutamate, aspartate, and gamma-aminobutyric acid (GABA) in brain tissue as well as plasma cyclic adenosine monophosphate (cAMP) were measured using assay kits. The ratio of reduced glutathione (GSH)/oxidized glutathione (GSSG) and Mn-superoxide dismutase (MnSOD) activity in brain mitochondrial fractions as well as mitochondrial glutathione reductase and cytosolic γ-glutamylcysteine activities were also examined. The phosphorylation of cAMP-responsive element binding protein (CREB) in brain tissue was measured by Western blot analysis. XEASD treatment was found to significantly ameliorate the severity of behavioral symptoms in affected mice, as evidenced by decreases in the stereotypy score and locomotor activity. The beneficial effect of XEASD was accompanied by the reversal of abnormal levels of GABA, glutamate, and aspartate, in brain tissue of IDPN-challenged mice. In addition, XEASD treatment increased plasma cyclic adenosine monophosphate (cAMP) levels and activated the phosphorylation of CREB in brain tissue of TS mice. Furthermore, XEASD treatment was found to enhance the antioxidant status of brain tissue in affected mice, as evidenced by increases in the GSH/GSSG ratio and the activity of MnSOD in brain mitochondrial fractions. Taken together, these experimental results will hopefully provide insight into the pharmacological basis for the beneficial effects of XEASD in children suffering from TS.